African and counter-colonial perspectives in criminology - Agozino, Biko (Southernising criminology, 2024)
This chapter addresses the domination of criminology by scholars in the colonising North and the relative neglect of the discipline in colonised Southern jurisdictions, contributing to the underdevelopment of the discipline, as theorised in Counter-Colonial Criminology (Agozino, 2003). The chapter questions whether top universities know what they taught to their graduates who went on to execute genocidal violence in the South. With a brief comment on Indigenous criminology, the chapter offers a critical review of Southern Criminology and the decolonial paradigm. The filling of the lacuna in critical criminology perspectives with texts like the Routledge Handbook on Africana Criminologies (Agozino et al., 2020) is noted. The chapter concludes with an outline of a program of action by intellectual activists in criminology to further the ongoing struggle for decolonisation worldwide. Following the articulation of race-class-gender dominance and resistance structures that may be different but are not separate in societies structured in dominance, according to Stuart Hall (1980), there is the need for coalition and alliance building as cultural means of struggle, therefore, the chapter calls on all criminology activists to support reparative justice for people of African descent.